Small Cell Carcinoma of the Uterine Cervix in a Pregnant Patient Diagnosed with Liquid Based Cytology and Cell Block Immunocytochemistry - Mawuli F. Attipoe; Charles D. Sturgis (Hindawi Limited, 2014)
Definitive cytomorphologic diagnosis of small cell carcinoma of the uterine cervix is possible but can be challenging in routine cervicovaginal cancer screening specimens. Several small series of reported cases of cervical small cell carcinoma have shown this uncommon malignancy to represent fewer than 2% of all invasive cervical cancers. This tumor type is associated with poor prognosis and rapid disease progression and can develop to an advanced stage in the interval between screening visits. Only rare case reports of small cell carcinoma arising in gravid cervices are known. In the current case a 29-year-old, gravida 6, para 2, pregnant (10-week gestation) female presented with postcoital bleeding. A definitive diagnosis of small cell carcinoma of the cervix was made possible by liquid based Pap testing with ancillary cell block preparation allowing for immunocytochemical characterization of the lesional cell population.